Avaliação da aplicação do sistema de leito de drenagem como tratamento de lodo da Estação Tratamento de Água Bom Jardim em Uberlândia-MG - Santos, Bruna (2013)
In Brazil, the Water Treatment Plants generates about 1 to 4 % of the waste volume compared to the volume of treated water. Although there are few WTP that have sludge treatment systems in Brazil, approximately 0.5 % of the WTP. Also in Brazil the major concern with the generation of waste by the Water Treatment Plants (WTP) is about the waste launching indiscriminate directly into waterbodies, mainly surface water sources. Since the launch of residues in surface waters there is a reduction in the quality of brute water and the formation of a vicious cycle characterized by the consequent increase in the use of chemicals in water treatment and the generation of an increasing volume of waste. In this sense this work have the objective to evaluate the performance of drainage and drying phases of the sludge from the WTP Bom Jardim by the sludge dewatering natural system Draining Bed (DB). For this, preliminary assays were performed with 16 geotextils, from these tests were selected three geotextiles which were used for the composition of Draining beds in the next assays. Therefore, the natural systems were evaluated when subjected to Application Rates of Solids (ARS) 1.75 kg.m-2, 3.5 kg.m-2 and 7.0 kg.m-2. Each assay was analyzed on drain and drying phases. In the drainage phase were evaluated parameters as true color, apparent color, turbidity, heavy metals (Fe, Pb, Cd, Cr, Al and Mn), COD and BOD. In the drying phase, the Draining Beds were evaluated in duplicate, so a system partially protected from climatic variables and the other completely exposed, the basis of which we analyzed the influence of climatic variables on sludge dewatering. Therefore, we found the great influence of these variables in the system, since the sludge of the system partially protected in all experiments presented well below percentage of solids, considering the same operation time. The comparative evaluation test with TAS 1.75 kg.m-2, 3,5 kg.m-2 and 7.0 kg.m-2, demonstrate that best results were obtained using the geotextile RT- 31 with ARS of 3,5 kg.m-2. The effluent had drained with 0.93 NTU of turbidity and the end of the seven days of drying time retained in the Draining Bed without wrap had 68.3 % lower levels of solids than in systems with wrap.